CONSERVATION TILLAGE PRACTICES FOR ENHANCED PRODUCTIVITY IN SUGARCANE–PADDY SYSTEM - K V , RAMANA MURTHY; P V K , JAGANNADHA RAO (The Journal of Research ANGRAU, 2026)
A field study was carried out at Regional Agricultural Research Station farm, Anakapallefrom 2022-23 to 2024-25 for three years to study the feasibility of conservation tillage practicesand its impact on crop establishment, growth of crop and weed, and productivity of Sugarcane inSugarcane-Paddy cropping system. The trial was carried out using a strip plot design with threereplications. The main plot factor comprised of conservation tillage practices and weedmanagement techniques in sub plots. The cropping cycle of sugarcane planting in furrows withridgemar in rice fallows + Cowpea during first year followed by Sugarcane (ratoon)+Cowpeaduring second year andtaking up Pulse-Green manure-Paddy with minimal tillage and sowingduring the third  year in addition to chemical weed control methods for effective weed managementwas found suitable to improve the overall productivity of Sugarcane-paddy system(217.47 t ha-1)and economically profitable instead of the normal conventional system.